The Influence of Education and Mentality on Entrepreneurial Motivation Through Attitudes of FEB UNM Students - Andi Reski Nurhikmah; Ulfa Amani Hidayati; Dwiyanti; Khaerun Nisa SH (Politeknik Caltex Riau, 2026)
Main Purpose – This study aims to analyze the influence of entrepreneurship education and entrepreneurial mindset on entrepreneurial motivation through entrepreneurial attitudes as a mediating variable in students of the Faculty of Economics and Business, Universitas Negeri Makassar Method – A quantitative approach with an explanatory design was used in this study through the distribution of questionnaires to 100 respondents. Samples were selected using proportional random sampling techniques and data were analyzed using the path analysis method Main Findings – The test results showed that entrepreneurship education had a significant effect on entrepreneurial attitudes, but did not have a direct effect on entrepreneurial motivation. On the other hand, the entrepreneurial mindset has been proven to have a significant direct effect on students' entrepreneurial attitudes and motivations. Furthermore, the path analysis proves that entrepreneurial attitudes function as a variable that mediates entrepreneurship education on entrepreneurial motivation. Theory and Practical Implications – Practically, these results indicate that higher education institutions need to reorient the curriculum from theoretical to strengthening psychological aspects and forming positive attitudes of students. Academic policies should better integrate business incubator programs and practical training to stimulate students' real encouragement in entrepreneurship. Novelty – The novelty of this research lies in proving the role of entrepreneurial attitudes as a mediating variable that explains why theoretical education requires the integration of psychological mindsets to be able to drive students' real motivation.